2018
DOI: 10.3389/fneur.2018.00300
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Kinematics in Stroke and Healthy Controls Using Target-to-Target Task in Virtual Reality

Abstract: BackgroundKinematic analysis using virtual reality (VR) environment provides quantitative assessment of upper limb movements. This technique has rarely been used in evaluating motor function in stroke despite its availability in stroke rehabilitation.ObjectiveTo determine the discriminative validity of VR-based kinematics during target-to-target pointing task in individuals with mild or moderate arm impairment following stroke and in healthy controls.MethodsSixty-seven participants with moderate (32–57 points)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…A movement segment was defined as time when a target appears to time when it disappears. Five kinematic variables were calculated: movement time, mean velocity, peak velocity, time to peak velocity and smoothness [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A movement segment was defined as time when a target appears to time when it disappears. Five kinematic variables were calculated: movement time, mean velocity, peak velocity, time to peak velocity and smoothness [26].…”
Section: Methodsmentioning
confidence: 99%
“…This measure distinguishes between the relative time spent during the first visually triggered outward movement until the peak velocity is reached (feedforward), and the second half of the movement toward the target that requires more precision in order to touch the target (feedback). In the second half of the movement, subjects tend to make multiple attempts to reach the target, resulting in the formation of spider-web like patterns in the movement trajectory [26]. The smoothness metric was calculated by counting the number of velocity peaks in a movement segment.…”
Section: Methodsmentioning
confidence: 99%
“…The age of the included subjects was 59 [40,53,69,88] years (median [minimum, 25 th -percentile, 75 th -percentile, maximum]) with 14 of them being female. FMA-UE scores for the most affected and less affected sides were 49 [32,40,57,61] and 65 [56,63,66,66], respectively. ARAT scores for the most affected and less affected sides were 47 [30,39,55,57] and 57 [45,57,57,57] , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…While these approaches are promising to relate sensorimotor impairments and activity limitations and further also allow to study compensatory trunk movements, the solutions rely on a costly and time-consuming measurement setup with an optical motion capture system, thereby having limited clinical applicability. Research towards more rapidly applicable approaches has also been proposed, for example relying on the same robotic end-effector as the VPIT [57,58]. However, the presented task did not require any precise object manipulations and relied on the regular handle of the end-effector that cannot record grip forces.…”
Section: Assessment Of Functionally Relevant Sensorimotor Impairmentsmentioning
confidence: 99%
“…Viau et al reported that patients with hemiparesis used less wrist extension and more elbow extension at the end of the placing phase during reaching, grasping, and performing tasks in VR than in a real environment [ 74 ]. Similarly, several studies using reaching tasks also demonstrated that the movements in VR using HMDs were slower than those in the real environment and that spatial and temporal kinematics differ between VR and real environments [ 75 , 76 , 77 ]. Lott et al reported that the range of the center of pressure during reaching in standing (usually used for balance training) was different between real environments, non-immersive VR with 2D flat-screen displays, and immersive VR with HMDs [ 78 ].…”
Section: Considerations For Vr Application In Stroke Rehabilitatiomentioning
confidence: 99%